Proliferative analysis of the Crandell-Rees Rim Feland cell (CRFK) grown with Dulbecco culture medium (DMEM) supplemented with B complex coenzymes (Research, Society and Development, 2020)
The cell culture technique is used by all areas of science, mainly in Biotechnology, as it brings precise results and knowledge on new pathologies, studies on mechanisms of infections by microorganisms. The aim of this study was to analyze the proliferative potential of the Crandell-Rees Feline Kidney (CRFK) cell in static culture with Dulbecco culture medium (DMEM) supplemented with complex B coenzymes. This is a quantitative experimental study, divided into three groups: Control, Diverse and Diverse with B12, where the Control group did not receive extra concentration of coenzymes, the Diversas group received treatment with complex B coenzymes, which are: thiamine, riboflavin, niacin, pantathenic acid, pyridoxine, biotin and acid folic acid in four different concentrations, always doubling the concentration in the package insert of the DMEM culture medium, the third group received all seven coenzymes of the B complex plus cyanocobalamin (B12) that is not present in the package insert of DMEM. From this study it was concluded that the treatment with complex B coenzymes optimized the process of mitosis and subcultures time: in the Diverse group with B12 the culture time was 19.05 hours to reach the optimum point of confluence when compared Control group. Therefore, the study pointed out that coenzyme B12 is essential for cell metabolism, optimizing culture time by increasing the potential for cell mitosis.